A Ser162→ Leu Mutation within Glycoprotein (GP) IIIa (Integrin β3) Results in an Unstable αIIbβ3 Complex that Retains Partial Function in a Novel Form of Type II Glanzmann Thrombasthenia - Jackson, Denise E.; White, Melanie M.; Jennings, Lisa K.; Newman, Peter J. (Thrombosis and Haemostasis, 1998)
Platelets from Glanzmann thrombasthenia patient BL express approximately 30% of the normal αIIbβ3 content and support fibrin-mediated clot retraction, but fail to bind fibrinogen or aggregate following cellular activation. BL platelets bind neither activation-dependent nor activation-independent ligands. DNA sequence analysis of BL platelet mRNA revealed a homozygous C583→T point mutation in a conserved region of β3, resulting in a Ser162Leu amino acid substitution. This mutation appears to produce destabilizing effects on the αIIbβ3 complex, as evidenced by the fact that (1) the BL αIIbβ3 complex exhibited altered sedimentation velocity through sucrose gradients, (2) αIIb and β3 was not recognized by complex-dependent monoclonal antibodies or co-precipitated by integrin subunit-specific antibodies, and (3) biosynthesis and trafficking of the αIIbβ3Leu162 complex was delayed relative to that of the wild-type control. Taken together, these data implicate the region encompassing Ser162 in the stabilization and ligand binding properties of the αIIbβ3 complex.